Estimativa da erodibilidade do solo para fins conservacionistas na microbacia córrego do tijuco, SP - Arraes, Christiano Luna [UNESP]; Bueno, Célia Regina Paes [UNESP]; Pissarra, Teresa Cristina Tarlé [UNESP] (My University, 2010)
The soil erodibility factor is represented by the integrated effect of processes that regulate the water infiltration, soil resistance and the transport of soil particles. Therefore, this study had as objective to estimate the soil erodibility in the Córrego do Tijuco watershed, São Paulo State, Brazil, for guiding farmers in decision making for application of techniques for soil conservation. The soil samples were collected in a regular spacing of 500 m, resulting in a total of 310 points in a 0-20.0 m depth in an area of approximately 8,000 ha. For the estimation of soil erodibility (K) was applied a mathematical model which takes into account the soil organic matter content, the sand and silt size fractions, the soil permeability, and the particle mean diameter for each point of soil sampling. Estimated values greater than 0.040 Mg ha h ha-1 MJ-1 mm-1 were considered very high for this factor. In areas with greater degree of erodibility occurs the Argisols order predominance, that shows high susceptibility to the development of interrill erosion due to its remarkable performance in relation to textural gradient, thereby, the interrill erosion rates can be very intensive due to rapid saturation of upper horizon, increasing the erosion process. At the Latosols (Oxisols) areas were also observed high soil erodibility values that under inappropriate conditions of soil occupation, concentrating runoff of rain water, leading to appear deep gullies.
Soil erodibility estimation for conversation planning in the córrego do tijuco watershed, Säo Paulo, Brazil
Keywords: Erosion; Textural gradient; Watershed